Partisipasi Karang Taruna Dalam Kegiatan Pemerintahan di Desa Jatimukti - Fillan, Nuni Andriani Zahra Sean; Raden Zahira Nisrina Naziha; Rifqi Jauhari (Fisip UIN Sunan Gunung Djati Bandung, 2023)
Karang Taruna is an organization that focuses on youth, the participation of Karang Taruna is very much needed in activities related to youth and village government activities. The purpose of this research is to find out how youth organizations participate in village government activities. The research method used is a qualitative method of data collection techniques carried out by means of interviews, observation, and documentation. The data analysis technique is descriptive qualitative with the following stages: data collection, data reduction, presentation and conclusion. The results obtained in this study (1) Youth Organization participation in village government activities are seen as aspects of program management using three dimensions 1) Contribution; 2) Organizing; 3) Community empowerment. (2) The participation of the Jatimukti Village Youth Organization in village government activities has been running as in annual activities, or activities held considering conditions. However, the participation of the Jatimukti Village Youth Organization has not run optimally because there are still barriers to Youth Youth Organizations who are less aware of their responsibilities. Thus there must be efforts to increase awareness of responsibility such as holding socialization of the importance of the role of youth organizations for village areas